LEKSEM VERBA TINDAKAN âMEMUKULâ DALAM BAHASA INGGRIS - , Dewi Ismu P ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The difficulties to identify the meaning of a lexeme have been the common problem in linguistics since the concept of meaning was introduced. Some lexemes have the similar meaning and relate one lexeme to the other one. On contrary, a lexeme can produce different meanings according to the context. This study aimed to find out the lexemes describing an action verb to hit in English, the meaning of those lexemes according to the context, and the types of relations from different meanings in a lexeme. This is a descriptive study. The data was collected from English dictionaries and website (www.webcorp.org.uk) using metode simak and teknik catat. It was analyzed using contrastive method and componential analysis technique to find out the semantic features of the lexemes describing the action verb âto hitâ in English. This study found they were forty nine lexemes describing an action verb âto hitâ in English. They were hit, bang, bash, batter, beat, belt, biff, blast, bludgeon, bonk, brain, bump, cane, clap, clobber, clout, club, conk, cosh, crack, crash, crown, cudgel, cuff, flog, hammer, jog, knock, lash, pound, pommel, punch, rap, slap, slug, smack, smash, smite, sock, spank, strike, swat, tap, thrash, thump, thwack, wallop, whack, and whip. The lexemes had eight semantic features. The use of these lexemes in the sentences produced the new meanings which were related to the dominant semantic features of lexemes. There were three types of relations from different meanings in a lexeme, (i) derivation, (ii) figurative extension, and (iii) peripheral clustering.